2019
DOI: 10.1039/c8nr09547g
|View full text |Cite
|
Sign up to set email alerts
|

Visible light to switch-on desorption from goethite

Abstract: Switching adsorption–desorption by visible light would provide the possibility for a wide range of applications that require controlled release-on-demand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…The bandgap value 2.33 eV for goethite (direct transition) was observed from optical absorption versus photon energy plots (αhν) 2 , as demonstrated in ESI Figure S2c. The observed bandgap value for goethite is in good agreement with previously reported values [25].…”
Section: Feooh → Fe O + H O (9)supporting
confidence: 92%
See 1 more Smart Citation
“…The bandgap value 2.33 eV for goethite (direct transition) was observed from optical absorption versus photon energy plots (αhν) 2 , as demonstrated in ESI Figure S2c. The observed bandgap value for goethite is in good agreement with previously reported values [25].…”
Section: Feooh → Fe O + H O (9)supporting
confidence: 92%
“…However, the photo-Fenton activity for hematite nanoparticles obtained by a thermal transformation from various iron-bearing nanoparticle precursors has not yet been studied so far. At the same time, there are broad research possibilities because several nanoparticle shapes have been synthesized for iron oxides and oxyhydroxides, for example, nanoplates [24], nanowires [25], nanostructured urchin-like hollow spheres [26] and nanotubes [27]. This allows one to potentially obtain a large variety of different hematite nanostructures, with a potential to produce highly active photo-Fenton catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…600 nm: 2.1 eV), [6d] or α‐FeOOH ( ca . 620–497 nm: 2.0–2.5 eV), [6e–f] which is confirmed as a by‐product. It also suggested that the broad absorption over ca .…”
Section: Resultsmentioning
confidence: 70%
“…α-Fe 2 O 3 was prepared by co-precipitation method followed by calcination, as described in our previous works [14,21]. Briefly, 0.1 M iron(III) nitrate solution was prepared, after adding a 0.4 M NaOH solution.…”
Section: Synthesis Of the Agmentioning
confidence: 99%